2010
DOI: 10.1186/1749-8546-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Duhuo Jisheng Tang containing Xixin safe? A four-week safety study

Abstract: BackgroundThough the nephrotoxicity and carcinogenicity of aristolochic acid (AA) are known, its safety in clinical usage is not clear. This study aims to evaluate the safety of Duhuo Jisheng Tang (DJT) in a four-week study to treat osteoarthritis (OA) of the knee.MethodsA qualitative and quantitative investigations on DJT were conducted. A list of adverse events (AEs), complete blood counts, and liver and kidney function tests were measured for participants with knee OA at their scheduled hospital visits. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…CM products (including CMM) could be applied according to the principles of diagnosis and treatment in CM, and based on that, CM practice can be considered as safe. There are various studies reporting the good safety of CM decoctions in the treatment of some chronic diseases [35][36][37][38][39]. Our survey also showed that both CM practitioners and patients believe that decoction is effective and safe (unpublished data).…”
Section: Has Been Proved To Be Relatively Safe In the Treatment Ofsupporting
confidence: 57%
“…CM products (including CMM) could be applied according to the principles of diagnosis and treatment in CM, and based on that, CM practice can be considered as safe. There are various studies reporting the good safety of CM decoctions in the treatment of some chronic diseases [35][36][37][38][39]. Our survey also showed that both CM practitioners and patients believe that decoction is effective and safe (unpublished data).…”
Section: Has Been Proved To Be Relatively Safe In the Treatment Ofsupporting
confidence: 57%
“…No acute renal tubular damage was observed after receiving four weeks of DJS (possibly a total of 1.34–2.01  μ g of AAI) during the study period [43]. Possibly, as compared to the reported case of the AA-related nephropathy that involved a patient ingesting 400 g of DJT for over four months, the ingestion levels of AA in our observational study were very low.…”
Section: Discussionmentioning
confidence: 69%
“…An experimental study showed that Du-Huo-Ji-Sheng-Tang could regulate the expression of the vascular endothelial growth factor mRNA and hypoxia-inducible factor -1α mRNA and inhibit chondrocyte apoptosis in an animal model (Chen et al, 2011a). Although no drug reactions or adverse events were observed during the study period (Hsieh et al, 2010), further research is required to provide more evidence for establishing its efficacy and safety.…”
Section: Discussionmentioning
confidence: 96%